ASSESSING USING TECHNOLOGY: IS ELECTRONIC PORTFOLIO EFFECTIVE TO ASSESS THE SCIENTIFIC LITERACY OF EVOLUTION THEORY - Prastiwi, M S; Kartowagiran, B; Susantini, E; Setiawan, B (Unnes Science Education Journal, 2019)
This study used a sequential exploratory mixed method to examine the effectiveness of using electronic portfolio to assess the scientific literacy of evolution theory. 135 university students majoring biology education were involved as the research participants. They were asked to create the electronic portfolio by using any learning artefacts produced during the classroom activities including direct and virtual practicums, reading activities, direct and online discussions, quizzes, and formative examinations. Results depicted that electronic portfolio was effective for assessing the scientific literacy of evolution theory that consisted of some skills namely scientific communication, observation and experiment, scientific and creative thinking, professionalism, and electronic portfolio organization and content. Another finding disclosed that students showed a positive response on the electronic portfolio creation. This study suggests that electronic portfolio can be used as an assessment tool of the scientific literacy of evolution theory relevantly to industrial revolution 4.0.